Effect of pesticide and other crop protection product mixtures on dicamba volatilization - Costa, Renato Nunes; Gomes, Giovanna Gimenes Cotrick; Palhano, Matheus; Barbosa, Henrique; Abbade Neto, Dyrson; Ovejero, Ramiro Fernando López; Velini, Edivaldo Domingues; Carbonari, Caio Antonio (Frontiers in Agronomy, 2025)
Dicamba is an important tool for managing hard-to-control weeds in Brazil. Its use has increased, especially with the adoption of dicamba-tolerant crops, making the implementation of best management practices essential to ensure safe herbicide application, whether alone or in combination with other products. This study evaluated the volatilization of dicamba (diglycolamine salt – DGA) applied alone or in tank mixtures with glyphosate potassium salt (GK), a volatility reducer (VR), and various commercial crop protection products, over corn straw under controlled conditions. Volatilized dicamba was collected for 24 h at 40 °C and quantified by LC–MS/MS (LOD = 0.09 ng mL-¹, LOQ = 0.39 ng mL-¹). The VR consistently reduced dicamba vapor losses by up to 90%, regardless of the mixture. Most tank mixes did not increase volatility relative to DGA + GK + VR, except for combinations with glufosinate ammonium and mesotrione + atrazine, which increased volatilization by 49% and 43%, respectively, compared to DGA + GK + VR, though still 70% lower than dicamba applied alone. These increases were likely related to ammonia release and interactions with amine groups, rather than pH differences. Findings demonstrate that VRs are effective for mitigating dicamba volatilization even in complex mixtures, but certain combinations require caution. Results provide practical guidance for tank-mix decisions and support the adoption of best practices to reduce volatility-related drift in dicamba-based weed control.